Pengaruh Brand Image dan Product Quality terhadap Repurchase Intention yang Dimediasi oleh Customer Satisfaction pada Produk Kopi dalam Kemasan Siap Minum Luwak White Koffie di Kota Bandung - Maulana, Iman; Marliani, Leni Evangalista (Universitas Batanghari, 2024)
This study aims to analyze the effect of Brand Image and Product Quality on Repurchase Intention mediated by Customer Satisfaction on ready-to-drink packaged coffee products Luwak White Koffie in Bandung City. This study used a questionnaire as a research instrument involving 120 respondents selected using convenience sampling techniques, including in the nonprobability sampling category. Data collection was conducted in a cross-sectional or one shot study. The research instrument was tested for validity and reliability. Data analysis was carried out using verification analysis which included multiple regression analysis and sobel test. Of the seven hypotheses proposed, all hypotheses are supported by empirical data. The results showed that Brand Image has a positive and significant effect on Customer Satisfaction, Product Quality has a positive and significant effect on Customer Satisfaction, Brand Image has no positive and significant effect on Repurchase Intention, Product Quality has a positive and significant effect on Repurchase Intention, Customer Satisfaction has a positive and significant effect on Repurchase Intention, and Customer Satisfaction does not mediate the effect of Brand Image or Product Quality on Repurchase Intention.